2003
DOI: 10.1128/iai.71.1.393-400.2003
|View full text |Cite
|
Sign up to set email alerts
|

CD36-Mediated Nonopsonic Phagocytosis of Erythrocytes Infected with Stage I and IIA Gametocytes of Plasmodium falciparum

Abstract: Gametocytes, the sexual stages of malaria parasites (Plasmodium spp.) that are transmissible to mosquitoes, have been the focus of much recent research as potential targets for novel drug and vaccine therapies. However, little is known about the host clearance of gametocyte-infected erythrocytes (GEs). Using a number of experimental strategies, we found that the scavenger receptor CD36 mediates the uptake of nonopsonized erythrocytes infected with stage I and IIA gametocytes of Plasmodium falciparum by monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 53 publications
(57 reference statements)
3
50
0
Order By: Relevance
“…For PfEMP-1, it has been suggested that immunity may regulate the densities of both gametocytes and trophozoites by antibody-dependent cell-mediated cytotoxicity reactions (354) and prevention of sequestration (90). The scavenger receptor CD36 was found to mediate the uptake of erythrocytes infected with early-stage gametocytes (I and IIa) by nonopsonic phagocytosis by monocytes and macrophages (436), as was previously shown in the phagocytosis of trophozoites and schizonts (267). In addition to proteins involved in erythrocyte adhesion, molecules on the surfaces of erythrocytes infected with mature gametocytes may also elicit immune responses and may be involved in the clearance of circulating gametocytes.…”
Section: Evidence For Immune Responses Influencing Gametocyte Concentmentioning
confidence: 75%
See 1 more Smart Citation
“…For PfEMP-1, it has been suggested that immunity may regulate the densities of both gametocytes and trophozoites by antibody-dependent cell-mediated cytotoxicity reactions (354) and prevention of sequestration (90). The scavenger receptor CD36 was found to mediate the uptake of erythrocytes infected with early-stage gametocytes (I and IIa) by nonopsonic phagocytosis by monocytes and macrophages (436), as was previously shown in the phagocytosis of trophozoites and schizonts (267). In addition to proteins involved in erythrocyte adhesion, molecules on the surfaces of erythrocytes infected with mature gametocytes may also elicit immune responses and may be involved in the clearance of circulating gametocytes.…”
Section: Evidence For Immune Responses Influencing Gametocyte Concentmentioning
confidence: 75%
“…24,2011 P. FALCIPARUM AND P. VIVAX GAMETOCYTES 379 become infectious to mosquitoes (243). Early-stage gametocytes (stages I and IIa) seem to depend on CD36 as the principal host ligand for gametocyte adherence (106,193,436); ICAM-1, CD49c, CD166, and CD164 receptors that are present in human bone marrow epithelial and stromal cell lines have been suggested as host ligands for later gametocyte stages (stages III and IV) (113,390). Parasite ligands that mediate adherence are less well characterized but may include the parasite surface proteins PfEMP-1 (P. falciparum erythrocyte membrane protein 1) (105,193,411), RIFIN (repetitive interspersed family) (17, 505), and STEVOR (subtelomeric variable open reading frame) (273,458).…”
Section: Sequestration Of Gametocytesmentioning
confidence: 99%
“…CD36 is transcriptionally regulated by the nuclear receptor peroxisome proliferator-activated receptor ␥-retinoid X receptor (PPAR␥-RXR) (18). PPAR␥-RXR agonists have been shown to increase CD36-mediated phagocytosis of IEs (12,14,15,17) and to reduce GPI-induced tumor necrosis factor alpha (TNF-␣) production (14,15) and have been proposed as potential therapeutics for malaria. However, before this can be explored it is important to investigate their effects on endothelial cell-parasite interactions.…”
mentioning
confidence: 99%
“…Plasmodial species are the causative organisms for Malaria which are injected into the host blood stream by Anopheles Mosquitoes during a blood meal [1,2]. Malaria has remained an age-long disease which has defied complete cure as a result of repeated re-infection [3,4].…”
Section: Introductionmentioning
confidence: 99%